2017
DOI: 10.4238/gmr16029110
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-6 gene polymorphisms and circulating levels with keloid scars in a Chinese Han population

Abstract: ABSTRACT. The aim of the present study is to explore the effect of IL-6 gene polymorphisms on the development of keloid scar (KS) in the Chinese Han population. Genotyping of IL-6 was performed by the polymerase chain reaction (PCR), followed by restriction fragment length polymorphism assays (PCR-RFLP). Serum level of IL-6 was measured using enzyme-linked immunosorbent assay (ELISA). Results indicated that when the IL-6 -572 CC homozygote genotype was used as the reference group, the GG genotype was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…In line with the findings of studies included in our systematic review, 28–31 Xue et al also demonstrated elevated IL‐6 levels in KFs 35 . Additionally, the IL‐6‐572 GG genotype was associated with an increased risk for keloids in an Egyptian, South‐Eastern Chinese and Japanese population 36–38 . Moreover, IL‐6 was significantly decreased in early foetal fibroblasts, possibly contributing to scarless healing 39,40 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with the findings of studies included in our systematic review, 28–31 Xue et al also demonstrated elevated IL‐6 levels in KFs 35 . Additionally, the IL‐6‐572 GG genotype was associated with an increased risk for keloids in an Egyptian, South‐Eastern Chinese and Japanese population 36–38 . Moreover, IL‐6 was significantly decreased in early foetal fibroblasts, possibly contributing to scarless healing 39,40 .…”
Section: Discussionsupporting
confidence: 86%
“…35 Additionally, the IL-6-572 GG genotype was associated with an increased risk for keloids in an Egyptian, South-Eastern Chinese and Japanese population. [36][37][38] Moreover, IL-6 was significantly decreased in early foetal fibroblasts, possibly contributing to scarless healing. 39,40 Interestingly, the corticosteroid triamcinolone, which is a first-line treatment of keloids, decreases IL-6 induced angiogenesis.…”
Section: Interleukins and Jak-stat Pathwaymentioning
confidence: 99%
“…When combining TA with IFN‐γ STAT3 inhibition and STAT1 induction may occur in parallel. In recent years is has been discussed whether IL‐6 overexpression as well as genetic analysis concerning IL‐6 polymorphisms can be used as potential prognostic tools to evaluate the risk of keloid development ; therefore it seems to be possible that counter regulating IL‐6 overexpression might be a critical trigger to inhibit the prolonged inflammatory phase of wound healing in keloids. Even though the relative TA‐dependent IL‐6 reduction was less pronounced in keloid fibroblasts than in normal fibroblasts it has to be considered that in clinical settings cytokine secretion of normal cells may also trigger paracrine response of the keloid cells by reducing the total cytokine concentration in the area surrounding the keloid.…”
Section: Discussionmentioning
confidence: 99%
“…Keloids are associated with IL-6 gene polymorphisms in Japanese and Chinese populations. [23][24] Furthermore, BM-MSCs reduce the level of IL-6 in a liver fibrosis model, suggesting that they may play the same role in keloids. [25][26][27]…”
Section: Inhibition Of Inflammatory Cell Infiltrationmentioning
confidence: 99%